Ectopia Cordis Associated with Pentalogy of Cantrell—A Case Report - Madi, José Mauro; Festugatto, José Roberto; Rizzon, Matheus; Agostini, Ana Paula; Araújo, Breno Fauth de; Garcia, Rosa Maria Rahmi (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Pentalogy of Cantrell (PC) is a rare congenital anomaly characterized by changes in the mesodermal median structures and congenital heart disease, often with a poor prognosis. In 1958, Cantrell et al2 defined the full spectrum of the syndrome with the following anomalies: defects of the anterior diaphragm, of the lower part of the sternum, of the supraumbilical region and the abdominal wall, of the diaphragmatic pericardium, and various intracardiac congenital abnormalities. The present report describes a case of ectopia cordis associated with PC and the importance of the participation of a multidisciplinary team in the treatment of this condition.
Keywords: ectopia cordis; pentalogy of Cantrell; abdominal wall defects; congenital heart defects; umbilical hernia